The spatial dimension of US house prices - Katharina Pijnenburg (Urban Studies, 2017)
Spatial heterogeneity and spatial dependence are two well established aspects of house price developments. However, the analysis of differences in spatial dependence across time and space has not gained much attention yet. This paper jointly analyses these three aspects of spatial data. A panel smooth transition regression model is applied that allows for heterogeneity across time and space in spatial house price spillovers and for heterogeneity in the effect of the fundamentals on house price dynamics. Evidence is found for heterogeneity in spatial spillovers of house prices across space and time: house prices in neighbouring regions spill over more in times of increasing neighbouring house prices then when neighbouring house prices are declining. This is interpreted as evidence for the disposition effect. Moreover, heterogeneity in the effect of the fundamentals on house price dynamics could not be detected for all variables; real per capita disposable income and the unemployment rate have a homogeneous effect across time and space.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer bundesweiten Konsortiallizenz in der Nachfolge einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. – This publication is with permission of the rights owner freely accessible due to an consortial licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Disposition effect; Heterogeneity in spatial dependence; Housing prices; Panel smooth transition regression